Giant Primary Choledocholithiasis: A Rare Case Report and Comprehensive Review of Literature - Samiksha Lamichhane; Suraj KC; Nishant Mishra; Shritik Devkota; Abhijeet Kumar; Rakesh Kumar Gupta (Clinical Case Reports)
ABSTRACT Choledocholithiasis is the second most common complication of gallstone disease. Giant primary choledocholithiasis is a rare occurrence. Ultrasonography is the initial mode of imaging, and endoscopic ultrasound is considered superior to other modalities. Endoscopic retrograde cholangiopancreatography can be used for stone extraction. Other treatment modalities include laparoscopic or open common bile duct (CBD) exploration. Many institutions in underdeveloped countries still practice open CBD exploration. Factors such as larger stone diameter, edema of the CBD, and the presence of multiple lithiasis can influence the treatment approach. In this article we are presenting a case of 62 years‐old‐female with no any known comorbidities had presented to emergency with severe upper quadrant pain and giant choledocholithiasis was diagnosed in ultrasound and computed tomography scan with no other features of complications and patient successfully underwent open CBD exploration with intraoperative choledochoscopy and primary closure.